2018
DOI: 10.1158/0008-5472.can-17-1076
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Drive Glycolysis in a Targetable Signaling Loop Implicated in Head and Neck Squamous Cell Carcinoma Progression

Abstract: Despite aggressive therapies, head and neck squamous cell carcinoma (HNSCC) is associated with a less than 50% 5-year survival rate. Late-stage HNSCC frequently consists of up to 80% cancer-associated fibroblasts (CAF). We previously reported that CAF-secreted HGF facilitates HNSCC progression; however, very little is known about the role of CAFs in HNSCC metabolism. Here, we demonstrate that CAF-secreted HGF increases extracellular lactate levels in HNSCC via upregulation of glycolysis. CAF-secreted HGF induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 51 publications
11
83
1
1
Order By: Relevance
“…Our findings confirm the results of a study from Kumar and colleagues [29]. They recently reported on HGF-related upregulation of glycolysis in HNSCC cells and further investigated the role of HGF/Met signaling in an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm the results of a study from Kumar and colleagues [29]. They recently reported on HGF-related upregulation of glycolysis in HNSCC cells and further investigated the role of HGF/Met signaling in an in vivo model.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown the influence of CAFs on the development of SCCHN, associating the expression of α-SMA with aggressive anaplastic tumours, advanced clinical stages, regional lymph node involvement, and recurrence of the disease (20,23). Moreover, CAFs has been outlined as a possible prognostic factor, considering that the inhibition of its activity has been shown to limit the progression of SCC in vitro and in vivo (24,25). Additionally, in our sample we observed a significant association between the expression of α-SMA and the primary tumour site, where cases of laryngeal SCC showed a greater presence of CAFs compared with oral SCC and nasosinusal SCC.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, bFGF induces OXPHOS in CAFs, leading to HGF production, thus closing the vicious circle. 58 In a clinical study, breast cancer patients with stage 0/1 tumors were treated with N-acetylcysteine (NAC) to reduce oxidative stress in stromal cells and decrease tumor growth. Interestingly, post-treatment biopsies showed that stromal (but not tumor) cells decreased expression of the lactate exporter MCT4 as a result of NAC treatment, while the proliferative index of tumor cells was reduced.…”
Section: Warburg Effec T In Tumor S Tromal Cell Smentioning
confidence: 99%